Influence of thickness and restorative material on the physicalmechanical behavior of CAD/CAM minimally invasive occlusal veneers - in vitro study - Maenosono, Edgar Massunari (2019)
The occlusal veneers consist in a minimally invasive restorative approach that aims to restore the shape and function of the posterior teeth affected by tooth wear. The aim of this study was to evaluate the behavior of the occlusal veneers when subjected to thermal and mechanical cycling. Sixty specimens were divided into 04 groups (n=15), showing two variation factors divided into two levels: material lithium dissilicate LD (IPS e.max CAD, Ivoclar Vivadent, Schaan, Liechtenstein) and nano ceramic resins NCR (ESPE Lava Ultimate, 3M, São Paulo, Brazil); thickness - 0.6 and 1.2mm. The occlusal veneers were luted with dual-polymerizing luting agent (Variolink N, Ivoclar Vivadent, Schaan, Liechtenstein) (RelyX Ultimate 3M, São Paulo, Brazil) using the respective adhesive system in self-etch mode. The resin cement was light cured for 40 seconds each face, using a LED light cure equipment that irradiates 1,100 mW/cm2 (BlueStar II, Microdont, São Paulo, Brazil). A response variable consists of veneer survival rates (crack formation, catastrophic cracks and debonding) when subjected to thermal cycling from 5 ° to 55 ° C for 1,000 cycles and simultaneous mechanical cycling performed at load intensities of 100, 200, 300, 400 and 450N for 20,000 cycles each. Data were submitted to the Kruskall Wallis test and Pairwise Comparison, adopting a significance level of 5%. NCRs presented a lower incidence of failures (p <0.05) when compared to LD. As for thickness, 1.2 mm thick occlusal veneers withstand higher cycling loads. Within the constraints of this study, we can conclude that NCR occlusal veneers with 1.2mm thickness presented superior physical-mechanical behavior and lithium dissilicate occlusal veneers with thickness lower than 1.2mm are more likely to fail.